The nasal microbiota is a potential diagnostic biomarker for sepsis in critical care units - Tan, XiLan; Liu, Haiyue; Qiu, Wen; Li, Zewen; Ge, Shuang; Luo, Yuemei; Zeng, Nianyi; Chen, Manjun; Zhou, Qiqi; Cai, Shumin; Long, Jun; Cen, Zhongran; et al. (Microbiology spectrum, 2024)
The important clinical significance of this study is that it compared the intestinal and nasal microbiota of sepsis with non-sepsis patients and determined that the nasal microbiota is more effective than the intestinal microbiota in distinguishing patients with sepsis from those without sepsis, based on the difference in the lines of nasal specimens collected.